Prevalence and antimicrobial drug resistance of gram-negative bacteria in dairy feed and water: a One Health concern - Arbab, Safia; Ullah, Hanif; Wang, Weiwei; Qadeer, Abdul; Aseeri, Abdullah A.; Alzahrani, Fuad M.; Alzahrani, Khalid J.; Alsharif, Khalaf F.; Zhang, Jiyu (Frontiers in Veterinary Science, 2025)
IntroductionDairy animals are continually at risk of infection due to exposure to contaminated environments, particularly through feed and water. The presence of Salmonella spp. and Escherichia coli in these sources poses a serious One Health concern due to their potential for antimicrobial resistance (AMR) and subsequent transmission to humans, animals, and the environment. This study was conducted to evaluate the prevalence of these pathogens and their resistance patterns in dairy farm feed and water samples.Materials and methodsA total of 160 samples, comprising 98 feed and 49 water samples, were collected from dairy farms. Isolates were identified using Gram staining, motility testing, and endospore staining, followed by confirmation with standard biochemical tests (IMViC). Antimicrobial susceptibility testing was carried out, and Multiple Antibiotic Resistance Index (MARI) values were calculated.ResultsOf the 144 analyzable samples, 76 (51.7%) tested positive for E. coli and 68 (46.3%) for Salmonella spp. E. coli showed the highest susceptibility to ampicillin, cefotaxime, and ciprofloxacin (19%), while Salmonella spp. demonstrated the highest susceptibility to cefpodoxime and ampicillin (17%). MARI values exceeding the 0.2 threshold were observed in 6 (7.8%) E. coli isolates and 4 (5.8%) Salmonella spp. isolates, suggesting high antibiotic exposure. The mean inhibition zones were 9.87 ± 6.16 mm for E. coli and 8.5 ± 5.34 mm for Salmonella spp., with minimal variation between the two species.ConclusionThe comparable prevalence and resistance patterns of E. coli and Salmonella spp. in dairy farm feed and water highlight the risk of antimicrobial-resistant bacteria dissemination across human, animal, and environmental domains. These findings underscore the importance of integrated monitoring systems, judicious antibiotic use, and coordinated stewardship measures within the One Health framework.